A META-HEURISTIC SOLUTION APPROACH FOR THE DESTRUCTION OF MOVING TARGETS THROUGH AIR OPERATIONS - Ucar, Ukbe; Isleyen, Selcuk Kursat (Univ Cincinnati Industrial Engineering, 2019)
Moving Target Traveling Salesman Problem is the problem of destruction of targets moving at certain angles and speeds by a constant velocity pursuer. The problem is applied in many fields, most common of them being production, defense and surveillance systems. Military operations are the most strategic branch of these application areas. In this study, a new solution algorithm based on simulated annealing is proposed for destruction of moving targets through air operations in minimum possible time. Six different heuristic algorithms, three of which were used for the first time, were developed for generating the initial solution of the algorithms, and the best two constructive heuristics were used as the initial solution in simulated annealing algorithm. The Taguchi method was utilized to determine the parameters in the algorithm. The effectiveness of the algorithm in terms of solution time and solution quality was tested on 20 instances with the number of targets ranging from 5 to 25. The results of the analysis indicated that both the proposed solution algorithm based on simulated annealing and constructive heuristics destroyed all the targets in all scenarios within acceptable time. In addition, it has been found that Simulated Annealing-Minimum Distance Heuristic Algorithm produces better results than Simulated Annealing-Minimum Time Heuristic Algorithm.
Keywords: moving target traveling salesman problem; defense system; simulated annealing; Taguchi method